Whale watching in Iceland - Thebo, M (2017)
I walk down the harbor to the decommissioned whaler and wheel the pram up the ramp. My mind winces away from Melville-induced images of the slaughter that took place on the wide boards of this deck. I don't want anything to spoil the moment. Libby Jo and I are setting to sea, not ten miles from the Arctic Circle. My five-month-old and I are in northern Iceland, as part of a research trip for my PhD novel.